2003
DOI: 10.1097/00129804-200303000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Vascular Access Team in an Acute Care Setting

Abstract: In today's ever-changing acute care setting, justifying the allocation of resources for development and implementation of a Vascular Access Team (VAT) can often be challenging. The Infusion Nurses Society (2000), which establishes standards of practice for the infusion nursing profession, states that "the profession itself must seek control of its practice to assure the quality of its services to the public. A profession's concerns for quality services reflects its commitment to serving the community." This ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 1 publication
0
20
0
6
Order By: Relevance
“…A VAT can be instrumental in developing a clinically relevant and sufficiently rigorous infusion therapy education program. 6,18 There are sufficient published studies that report improved patient outcomes with the implementation of each of the elements of the IHI CLB to support inclusion of these interventions in the bundle. For example, the use of maximal barrier precautions during catheter insertion has been adopted as an element of the CLB based on studies completed in the early 1990s, which reported that the application of maximal barrier precautions substantially reduced the odds of developing a bloodstream infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A VAT can be instrumental in developing a clinically relevant and sufficiently rigorous infusion therapy education program. 6,18 There are sufficient published studies that report improved patient outcomes with the implementation of each of the elements of the IHI CLB to support inclusion of these interventions in the bundle. For example, the use of maximal barrier precautions during catheter insertion has been adopted as an element of the CLB based on studies completed in the early 1990s, which reported that the application of maximal barrier precautions substantially reduced the odds of developing a bloodstream infection.…”
Section: Discussionmentioning
confidence: 99%
“…The value of an effective VAT can be measured in improved patient care and outcomes as well as in cost savings for the facility that initiates such a team. 5,6 Effective VATs recognize the benefit of implementing the IHI CLB, and it is the duty of most VATs to enforce strict adherence to the CLB. In addition, an effective team strives to continually improve upon the interventions dictated by the CLB through the investigation of practice improvements and technology developments that will enhance the effects of the CLB on lowering catheter complications.…”
mentioning
confidence: 99%
“…4 There are not many specialty functions that touch such a broad population, yet few institutions have specialty infusion and vascular access departments that provide vascular access and infusion procedures and specific education to staff, patients, and families at an organizational level. It is estimated that 95% of patients will have some form of intravenous therapy or venipuncture procedure during a visit to an acute care facility.…”
Section: Background and Relevancementioning
confidence: 99%
“…Dedicated vascular access teams have demonstrated improvement in patient safety, better catheter outcomes and a reduction in catheter related nosocomial infections (Sharpe 2006). Nurse-led vascular access teams have also demonstrated improvements in hospital efficiency (Hunter 2003).…”
Section: The Nursing Role In the Insertion And Management Of Central mentioning
confidence: 99%